Phosphatase POPX2 interferes with cell cycle by interacting with Chk1 - Kim, Pu Rum (2022)
Protein-protein interaction network analysis plays critical roles in predicting the functions of target proteins. In this study, we used a combination of SILAC-MS proteomics and bioinformatic approaches to identify Checkpoint Kinase 1 (Chk1) as a possible POPX2 phosphatase interacting protein. POPX2 is a PP2C phosphatase that has been implicated in cancer cell invasion and migration. From the Domain-Domain Interaction (DDI) database, we first determined that the PP2C phosphatase domain interacts with Pkinase domain. Subsequently, 46 proteins with Pkinase domain were identified from POPX2 SILAC-MS data. We then narrowed down the leads and confirmed the biological interaction between Chk1 and POPX2. We also found that Chk1 is a substrate of POPX2. Chk1 is a key regulator of the cell cycle and is activated when the cell suffers DNA damage. Our approach has led us to identify POPX2 as a regulator of Chk1 and can interfere with the normal function of Chk1 at G1-S transition of the cell cycle in response to DNA damage.